Innovación institucional y democracia participativa: Mapeo legislativo de la Enmienda del Programa de Metas - Gaspardo, Murilo [UNESP]; Ferreira, Mauro [UNESP] (FapUNIFESP (SciELO), 2017)
The purpose of this article is to investigate the institutional innovation represented by the implementation of Programs of Goals in Brazilian cities through amendments in legislation, focusing on its contribution to the social control of public policies. The article presents a mapping on legislation based on the theory of participatory democracy. After a theoretical reflection about the limits of representative democracy and the search for institutional innovations in participatory democracy, the article presents a historical-legislative overview about the Goals’ Program and a comparative analysis of the normative texts that instituted it in Brazilian cities. As main results, in addition to a mapping that indicates the state of the art of the subject, we have the formulation of relevant hypotheses for the execution of legislative evaluation and development of proposals to improve the legal-institutional design of the object of investigation.
Inovação institucional e democracia participativa: Mapeamento legislativo da Emenda do Programa de Metas
Institutional innovation and participatory democracy: Mapping on legislation regarding the implementation of programs of goals in brazilian cities
Keywords: Goals’ program; Institutional innovation; Participatory democracy; Social control